(untitled) (International Educators Conference, 2025)
This article explores the interrelation, distinction, structure, and implementation of law-making policy and law-making strategy within the context of Uzbekistan’s legal reforms. The author emphasizes that law-making policy is not limited to legislative activity alone, but also serves as a political and social mechanism that sets strategic directions for societal and state development. The article highlights the essential features of a law-making strategy, including long-term legal and social needs assessment, phased and systematic development of legal institutions, and the use of scientific forecasting and expert analysis. Drawing from the experience of Uzbekistan, the author critically evaluates the current shortcomings in institutionalized legislative planning. The paper argues for the necessity of aligning strategic and tactical levels of law-making policy, where effective legislation must be based on both conceptual foresight and concrete implementation mechanisms. Furthermore, it underlines that the quality of legal norms is crucial to the construction of a democratic and legal state. The article concludes that the success of legislative policy depends on its coherence, systematic planning, and alignment with national priorities and socio-economic realities.